Species-Level Versus Community-Level Responses to Microhabitat Type and Diversity in an Experimental Plant Community - Bing Hu; Zhu-Wen Xu; Wei Xue; Fei-Hai Yu (Diversity, 2022)
Soil heterogeneity has been theoretically predicted to promote plant performance, but empirical evidence is often mixed. By focusing on a gradient of microhabitats (single, three and six types of microhabitats), we tested the hypothesis that increasing the number of microhabitats promotes the diversity and productivity of plant communities. We created different types of microhabitats by adding different forms of nitrogen (<semantics><msubsup>NH4+</msubsup></semantics>, <semantics><msubsup>NO3−</msubsup></semantics> and glycine) or combinations of these nitrogen in an even or patchy way. Community biomass, but not evenness, differed in different types of single-microhabitat. Increasing the number of microhabitat types did not alter community growth or evenness, but it increased the difference in the relative abundance of plant species within the community. These results suggest that microhabitat diversity can influence plant competitive hierarchies, and that this effect can lead to changed community growth, but may not be decisive for plant evenness.